A scoping review of published reports of the infection prevention and control assessment framework: a comparison to the findings of the global report on infection prevention and control - Zimmerman, Peta-Anne; Mason, Matt (International Journal of Infection Control, 2025)
Background: The World Health Organization (WHO) published the Global Report on Infection Prevention and Control (IPC) in 2022, highlighting both achievements and areas for improvement in IPC practices globally. The Infection Prevention and Control Assessment Framework (IPCAF) is a tool used to evaluate IPC programs across different healthcare settings. Aim: This scoping review aims to identify published reports of IPCAF use, collate available data, and compare findings to those of the WHO’s Global Report on IPC. Methods: A scoping review methodology was employed, involving searches in PubMed, MEDLINE via Ebsco, CINAHL via Ebsco, Embase via Ovid, and Scopus from November 2016 to March 2024. Studies included were surveys, cross-sectional studies, before-after studies, observational studies, or cohort studies published in peer-reviewed journals. Data extraction focused on study characteristics, IPC Core Component results, and overall IPCAF scores. Results: Twenty-seven articles met the inclusion criteria, representing 18 countries across four WHO regions. High-income countries (HICs) like Germany, Austria, and Japan reported predominantly Advanced IPCAF scores. In contrast, low-income countries (LICs) such as Sierra Leone, Uganda, and Ethiopia often reported Basic or Inadequate scores. Lower-middle-income countries (LMICs) like India, Indonesia, and Pakistan showed mixed results, while upper-middle-income countries (UMICs) like Türkiye and China generally reported higher scores. The review highlighted significant variability in IPC scores within and between countries. Conclusion: The findings corroborate the WHO’s Global Report, emphasizing the need for tailored interventions to enhance IPC practices, particularly in resource-limited settings. Addressing gaps in data collection and increasing participation from underrepresented regions are crucial for developing a robust global IPC framework.